Note—On the Optimal Packaging Frequency of Products Jointly Replenished - Andres, Fred M.; Emmons, Hamilton (Management Science, 1976)
Goyal [Goyal, S. K. 1974. Determination of the optimum packaging frequency of items jointly replenished. Management Sci. 21 (4, December) 436–443.] proposes an algorithm for the purposes of determining the optimal packaging frequency of products that may be jointly replenished. Each time a packaging run is made, costs include a fixed setup cost independent of the number of products packaged, plus an extra setup cost for each product packaged. Holding costs are assumed constant per unit of product per unit time, demand per item is constant, and no back-logging is allowed. While Goyal's algorithm probably gives a good solution, we note some shortcomings.